PREPARATION AND CHARACTERIZATION OF NEW IMINE- FUNCTIONAL GROUP FOR FAST REMOVAL OF Cr (III) IN SOME SUPPLEMENTS FROM SHRIMP SHELL - H. Y. Sharef,; N. A. Fakher, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A new imine-Schiff base adsorbent is prepared from extracted chitosan to make taking away exoskeletons of crustacean shrimp shells low-cost and environmentally friendly with the fast and high ability to remove Cr (III) from aqueous solution. The resulting composites were verified by different techniques FTIR, H-NMR, FESEM, EDX, XRD. On applying the adsorption kinetic model, the pseudo 2nd order model was best characterised, using adsorption equilibrium data; the Langmuir model provided a superior description. Further, the negative value of ∆G shows a spontaneous process in nature. Finally, the prepared adsorbent has been applied to a real sample of bodybuilder supplements.